IMPROVING THE COMPETENCE OF TEACHERS IN MAKING CLASSROOM ACTION RESEARCH THROUGH MGMP IN SMP NEGERI 23 PONTIANAK - ., Saryana (Universitas Tanjungpura, 2014)
The duties and obligations of teachers in addition to educate as well as researchers, the research attempted amending the learning. One of the forms was to improve the competence in conducting research was by means of Musyawarah Guru Mata Pelajaran (MGMP). This activity aimed to improve the competence of teacher in creating classroom action research, expectedly being able to improve the quality of learning process for teachers in the classroom, and improve student learning outcomes eventually. This research was conducted at SMP Negeri 23 Pontianak on September until December 2012. The subject of research was the teachers of SMP Negeri 23 about 27 people. This research was carried out using school action research design, designed through 3 cycles, each cycle through these steps: planning, implementation, observation and reflection. The competence of teacher in using classroom action research in cycle I is 38,82% in low categories. The competence of teachers in using classroom action research in cycle II is 78,33% in very high category. It was concluded that the competence of SMP Negeri 23 Pontianak inÂ classroom action research from cycle I to cycle II increase of 39,51%. From 27 teachers in SMP Negeri 23 Pontianak, who finished doing classroom action research to the number of 14 people. The number of teachers who did not conduct classroom action research to the number of 4 people. There were 2 teachers who could only follow 1 section. As many as 7 teachers could follow more than 2 times but they did not finish to make reports. At the beginning state before following the MGMP in SMP Negeri 23 Pontianak there were 2 teachers had ever done research and after following the MGMP there were 14 teachers who finished doing the classroom action research. There was raising in number of teachers who had the competency to do classroom action research as many as 12 people. It is concluded that once made MGMP at SMP Negeri 23 Pontianak is increasing the competence of teachers in making classroom research action as many as 12 people. Â Kata kunci: kompetensi membuat PTK